PENINGKATAN KEMAMPUAN MENGENAL SIMBOL HURUF MELALUI PERMAINAN MYSTERY BOX PADA ANAK USIA 4-5 TAHUN - Handriani, Marini; Darnis, Syefriani (Jurnal Caksana : Pendidikan Anak Usia Dini, 2021)
This study aims to determine the increase in the ability to recognize letter symbols through mystery box games in children aged 4-5 years at BKB Paud Melati 17, Klender, Duren Sawit, East Jakarta, 2019/2020 school year. This type of research is a classroom action research conducted in 2 cycles. The subjects in this study were students aged 4-5 years in 1 learning class. Data collection techniques are done by interview, observation and documentation. The research instrument used was an observation instrument the ability to recognize letters. The data analysis technique uses quantitative descriptive. With the mystery box game can improve the ability of students to recognize and mention the symbols of letters, namely children are invited to guess and mention pictures or objects and then mention the initial letters and pair letters with images. The results showed that there was an increase in students' ability to recognize and mention letter symbols, namely in the initial conditions of 29.72% then increased in Cycle I to 62.22% and Cycle II increased again by 84.86%.